Characterization of biopolymers based antibacterial films enriched with thyme essential oil and their application for milk cake preservation - Mulla, Mehraj Fatema Z.; Ahmed, Jasim; Vahora, Aateka; Pathania, Shivani; Rashed, Mahmoud Said (Frontiers in Food Science and Technology, 2024)
Polysaccharide based packaging and its ever increasing application in response to the need for sustainable and safe packaging has prompted researchers to deep dig into the development of antimicrobial biopolymer-based packaging for shelf life enhancement of food samples. A film with good mechanical properties i.e. tensile strength of 7.43 MPa and elongation at break of 23.033% was made by blending chitosan and pectin. To produce active packaging, thyme essential oil (TEO) was added to the blend at concentrations of 10%, 15%, and 20%. Films with added TEO showed significant enhancements in elongation at break (28.22%) and water vapor barrier properties (30.08 g/h.m 2 ). Additionally, the microstructure of the film was also improved, as demonstrated by SEM and AFM measurements. Fourier transform infrared spectroscopy (FTIR) indicated the interaction of blended matrix (chitosan and pectin) and TEO as observed from the formation of hydrogen bonds with the addition of TEO owing to the OH functional groups. The use of TEO in pectin and chitosan-based film and its application for milk cake packaging showed delayed microbiological contamination and hardness of milk cake samples. Further, the shelf life of milk cake packaged in pectin and chitosan blend film with 20% TEO was enhanced by >10 days.